Training and Mentoring Students of Institut Kesehatan dan Bisnis Surabaya (IKBIS) to Awake the Entrepreneurial Soul and Become Successful Entrepreneurs - Wibowo, Teguh Setiawan; Hariyanto, Ahmad; Hidayati, Nurul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of training and mentoring activities for Institut Kesehatan dan Bisnis Surabaya (IKBIS) students is to awaken the entrepreneurial spirit and become successful entrepreneurs is to foster an entrepreneurial mentality, improve practical skills, and have the knowledge to access resources and encourage innovation in developing new products . The methods used the theoretical presentation sessions, questions/answers and discussions for online training and discussions, FGDs, workshops and case studies for offline mentoring at the Surabaya Institute of Health and Business which were conducted on 92 Entrepreneurial students of Institut Kesehatan dan Bisnis Surabaya (IKBIS). The result is community service through training and mentoring activities for Institut Kesehatan dan Bisnis Surabaya (IKBIS) students to awaken their entrepreneurial spirit and become successful entrepreneurs, receiving an enthusiastic and positive response from the participants present. It is hoped that graduates of the Entrepreneurial Institut Kesehatan dan Bisnis Surabaya (IKBIS) students will have a deep understanding of the market, have strong practical skills in establishing or managing a business, have the ability to think creatively and innovatively and contribute positively to society, especially through the creation of new jobs.